2016
DOI: 10.1038/ncomms11605
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic transcriptional and translational landscape of the model antibiotic producer Streptomyces coelicolor A3(2)

Abstract: Individual Streptomyces species have the genetic potential to produce a diverse array of natural products of commercial, medical and veterinary interest. However, these products are often not detectable under laboratory culture conditions. To harness their full biosynthetic potential, it is important to develop a detailed understanding of the regulatory networks that orchestrate their metabolism. Here we integrate nucleotide resolution genome-scale measurements of the transcriptome and translatome of Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
229
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(258 citation statements)
references
References 44 publications
29
229
0
Order By: Relevance
“…For example, even well characterized Streptomyces species display complex gene expression profiles depending on culture conditions, because they have complex sigma factors and elaborate gene expression control systems. [176] Also, a significant proportion of bacteria which potentially are capable of producing valuable polyketides are noncultivable in laboratory conditions. This severely has discouraged the identification and the commercialization of important novel polyketides.…”
Section: Introductionmentioning
confidence: 99%
“…For example, even well characterized Streptomyces species display complex gene expression profiles depending on culture conditions, because they have complex sigma factors and elaborate gene expression control systems. [176] Also, a significant proportion of bacteria which potentially are capable of producing valuable polyketides are noncultivable in laboratory conditions. This severely has discouraged the identification and the commercialization of important novel polyketides.…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of RNA sequencing to analyse the global transcription profile, and ribosome profiling (ribo-seq) to analyse translation, a near-comprehensive gene expression picture of S. coelicolor at different stages of growth in liquid culture has been obtained 122 . This survey identified most of the transcription start sites in the entire genome, including those for 230 small RNAs.…”
Section: A High-resolution Global Survey Of Gene Expression In S Coementioning
confidence: 99%
“…Microarrays also revealed that 12 of 18 BGCs were expressed in wild-type Myxococcus xanthus , thus suggesting that many orphan BGCs may not be transcriptionally silent[31]. More recently, next-generation sequencing was employed in the global transcriptome analysis of S. coelicolor [32]. This study provided important new insight into the relationships between transcription and translation, something that remains poorly understood in the context of NP biosynthesis.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Furthermore, translation efficiencies can vary and thus expression alone is unlikely to be an adequate predictor of protein or NP production. For example, a recent study in S. coelicolor revealed that the transcription of several BGCs increased throughout growth yet their translation efficiency decreased at certain times[32]. It is also interesting to consider how the abundance of various tRNAs can affect translation efficiencies[36] and how a mutation in bldA , which is predicted to encode a misfolded Leu-tRNA molecule, can have a profound effect on BGC expression[37].…”
Section: Transcriptomicsmentioning
confidence: 99%